1987
DOI: 10.1002/ssu.2980030211
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance in relatives of patients with adenomatous polyposis

Abstract: Registry ascertainment of kindreds with adenomatous polyposis (AP) reduces the incidence of colorectal carcinoma by medical monitoring for offspring and siblings of affected patients. Due to its pleiomorphic genotype and a 50% risk for AP in each patient's progeny, early screening is mandatory. Flexible sigmoidoscopy, averaging from puberty to age 48, annually or every two years, is one diagnostic technique that does not result in excess patient discomfort or cost. Timely examination is facilitated when eye an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Thirty studies compared CRC incidence and/or mortality in screened and symptomatic groups in FAP including 8016 individuals ( Table S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty studies compared CRC incidence and/or mortality in screened and symptomatic groups in FAP including 8016 individuals ( Table S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Gebert and colleagues 22 demonstrated that screening reduced CRC incidence from 65.9 to 10.0 per cent, although no methodology was included in the review, limiting quality assessment. Berk and co-workers 24,33 found a tenfold reduction in CRC incidence between symptomatic and screened groups (57.0 versus 5 per cent).…”
Section: North America and Canadamentioning
confidence: 97%
See 1 more Smart Citation
“…15 Groups from North America, Denmark, Sweden, and Japan have all presented similar results highlighting the importance of the development of registry programs. 4,12,13,18 A recent systematic review regarding the implementation of screening and registry programs, including more than 8,000 patients in 33 published studies, all 33 showed a significant mortality benefit and decrease in the risk of CRC development. 19 Screening recommendations for patients with adenomatous polyposis syndromes have been addressed by several groups.…”
Section: Screeningmentioning
confidence: 99%